Strategi Pengelolaan Sarana dan Prasarana untuk Meningkatkan Motivasi Belajar Siswa - Mawaddatul Millah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The lack of management strategies for facilities and infrastructure in an educational institution can have a negative impact on student learning motivation The purpose of this study is to analyze how good management of facilities and infrastructure can increase student learning motivation. The method used is a literature study by reviewing various relevant literature sources. The results show that the existence of adequate facilities and infrastructure, such as good classrooms and supporting facilities, contributes significantly to increasing student learning motivation. The implications of these results highlight the importance of paying attention to the quality and management of school facilities and infrastructure to foster student engagement in learning. Therefore, improvement and innovation of facilities and infrastructure can be an effective strategy for schools and stakeholders to achieve better learning outcomes.